Ulcerated amelanotic melanoma of the ear in an 11 year old with Fitzpatrick VI skin type: A case report. (13th August 2021) - Roberts, Matthew; Moxham, J. Paul; Gregory, Allison; Armstrong, Linlea; Terry, Jefferson; Courtemanche, Douglas; Harvey, Melissa; Rehmus, Wingfield
Abstract: Melanoma is rare in pediatric patients and even more so in those with darker Fitzpatrick skin types. Although risk factors for conventional melanoma are similar in both adult and pediatric cases, the presentation of melanoma in pediatric patients is often distinct from adults. Here, we describe a case of amelanotic ulcerated nodular melanoma with regional lymph node metastases treated with nivolumab in a patient with Fitzpatrick skin type VI.